1998
DOI: 10.2527/1998.761228x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of volatile compounds on consumption of alfalfa pellets by sheep.

Abstract: We examined the effects of six volatile compounds on alfalfa pellet consumption by lambs. In each experiment, 45 lambs were individually fed alfalfa pellets sprayed with a selected compound (camphor, limonene, cis-jasmone, beta-caryophyllene, borneol, or alpha-pinene) at one of five concentrations. Treatment concentrations were multiples (0, .5, 1, 2, and 10) of the concentration of a specific compound (X) that was related to differential herbivory of tarbush by livestock in previous studies. Treatments were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
0
3

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 0 publications
3
37
0
3
Order By: Relevance
“…Hirasa and Takemasa (1998) reported that while some EO have inhibited bacterial growth (Hirasa and Takemasa, 1998), others seem to have improved nutrient utilization. When different levels of individual EO were sprayed on alfalfa pellets in sheep diets, intake was linearly reduced by camphor and a-pinene, quadratically increased by borneol and unaffected by h-caryophyllene, cis-jasmone and limonene (Estell et al, 1998). However a subsequent study found no effect of camphor or a-pinene on intake (Estell et al, 2005).…”
Section: Feed Intake and Apparent Digestibilitymentioning
confidence: 90%
“…Hirasa and Takemasa (1998) reported that while some EO have inhibited bacterial growth (Hirasa and Takemasa, 1998), others seem to have improved nutrient utilization. When different levels of individual EO were sprayed on alfalfa pellets in sheep diets, intake was linearly reduced by camphor and a-pinene, quadratically increased by borneol and unaffected by h-caryophyllene, cis-jasmone and limonene (Estell et al, 1998). However a subsequent study found no effect of camphor or a-pinene on intake (Estell et al, 2005).…”
Section: Feed Intake and Apparent Digestibilitymentioning
confidence: 90%
“…Behaviour and feed intake may also be effected by aroma. Estell et al (1998) demonstrated that terpene volatiles could effect feed intake in sheep. Varying levels of camphor (4) and a-pinene (5) (Fig.…”
Section: Feed Intake and Behaviourmentioning
confidence: 99%
“…[3,5] Estell et al [47] reported that terpene volatiles could aff ect feed intake in sheep, which is quite important when grazing in Mediterranean pastures. Better knowledge of specifi c chemical interactions with feed intake would be useful for altering feeding management.…”
Section: Growth-promoting Eff Ects and Palatabilitymentioning
confidence: 99%